Intravenous meropenem stability in physiological saline at room temperature. Issue 4 (4th April 2014) - Mollá-Cantavella, Sara; Ferriols-Lisart, Rafael; Torrecilla-Junyent, Teresa; Alós-Almiñana, Manuel
Abstract : Objectives: To evaluate the stability of solutions of 6 mg/mL, 8 mg/mL and 12 mg/mL meropenem in 0.9% NaCl in a polyolefin container (Viaflo), at room temperature, with a view to allowing extended or continuous perfusion in clinical practice. Methods: Meropenem was assayed using high-performance liquid chromatography. The technique was validated according to the criteria of the European Medicines Agency. Meropenem stability was evaluated for three different concentrations (6 mg/mL, 8 mg/mL and 12 mg/mL) at room temperature and during 48 h. The pH of the solution and its organoleptic properties were also evaluated. Results: The analytical technique abided with the specifications of the European Medicines Agency. The maximum accuracy and precision were 10% and 7.9%, respectively. The limit of detection was 0.000185 mg/mL and the limit of quantification 0.000562 mg/mL. The t90 for the dilution of 6 mg/mL of meropenem was 18 h (95% CI 14 h to 22 h), while the values for the 8 mg/mL and 12 mg/L concentrations were respectively 22 h (95% CI 19 to 32 h) and 17 h (95% CI 13 h to 21 h). The differences were not statistically significant (p<0.05). No variations in pH were seen. Conclusions: The results confirm the stability of the solutions of 6 mg/mL, 8 mg/mL and 12 mg/mL meropenem in 0.9% NaCl stored in a polyolefin container at 25°C for at least 12 h, thereby allowing their use as an extended or continuous perfusion.